Muscle twitch torque during two different in volume isometric exercise protocols: fatigue effects on postactivation potentiation - Xenofondos, A.; Bassa, E.; Vrabas, I. S.; Kotzamanidis, C.; Patikas, D. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to quantify the effect of the contraction duration of 2 isometric exercise protocols on the postactivation potentiation of 14 well-trained men (age: 22.6 ± 2.8 years, height: 180.3 ± 5.9 cm, and body mass: 72.3 ± 37.9 kg). The protocols consisted of 4 × 6 maximal plantar flexions, of 3-second (P3) or 6-second (P6) duration, performed in random order, with a 2-minute and 15-second intervals between the sets and repetitions, respectively. The torque during maximal isometric voluntary contraction (MIVC), the peak twitch torque (TT), and the rate of torque development (RTD) after each MIVC were analyzed for the first and the last trial of each set, the average of all trials of each set, and the trials within each set that had the highest peak TT. The MIVC had an overall greater reduction during P6 compared with P3 (P3: -4.6 ± 2.3 vs. P6: -16.0 ± 1.9%). P6 showed higher potentiation in TT during the initial repetitions of the first 2 sets (p < 0.05) in contrast to the P3, which revealed a lower potentiation but for a longer period along the exercise session. However, both protocols had on average the same potential for potentiation (P3: 81.6 ± 6.1 vs. P6: 79.8 ± 6.3%). The twitch RTD presented no systematic difference between the 2 protocols (p > 0.05). These data demonstrate the dependence of the TT potentiation on the conditioning stimulus and verify the cumulative effect of potentiation, suggesting the implementation of longer contractions to achieve maximal but temporal TT potentiation and shorter contractions for less variable but prolonged potentiation.